PENGGUNAAN MEDIA AUDIO BERBASIS APLIKASI UNTUK ANAK BERKEBUTUHAN KHUSUS TUNANETRA DALAM PEMBELAJARAN BAHASA INDONESIA SECARA DARING - Bella Ananda Dwi Umifa; Hespi Septiana; Dona Ananda; David Widyanto Putra (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to determine the use of application-based audio media and to determine the quality of application-based audio media for children with special needs with visual impairment. This study uses a qualitative approach with a descriptive method. Sources of data in this study were students with visual impairments. The data collection technique in this study used the literacy method (library study) by reviewing various literatures related to the use of audio media, education of children with special needs (Inclusive Education), and learning media. The results of this study are the use of audio media for blind children in learning Indonesian online is easy and can improve listening skills and application-based audio media has good quality seen from its easy use, economical cost, and has benefits that can help children with needs. specifically for the blind in learning Indonesian online. Keywords: visually impaired, audio, online